2019
DOI: 10.3389/fmicb.2019.02284
|View full text |Cite
|
Sign up to set email alerts
|

The Compromised Mucosal Immune System of β7 Integrin-Deficient Mice Has Only Minor Effects on the Fecal Microbiota in Homeostasis

Abstract: The gastrointestinal tract is an ideal habitat for diverse bacterial species that reside in a homeostatic balance with local tissue and significantly contribute to host health. Negative shifts in gut microbiota profiles, also known as dysbiosis, may be implicated in the development of chronic disorders such as inflammatory bowel diseases (IBD). Adhesion molecule-dependent recruitment of immune cells to the gut is an important step in IBD pathogenesis. The adhesion molecule β7 integrin contributes to the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Muribaculaceae is a freshly renamed family, which is formerly named as S24-7 . It has been reported that Muribaculaceae is positively correlated with immune response including natural killer cell and NF-κB signaling, and the family members of Muribaculaceae can interact with both innate and adaptive immune responses via IgA coating . Rikenellaceae, reported to present a higher relative abundance in ovalbumin/staphylococcal enterotoxin B-sensitized mice, was found to be reduced by AA-2βG in our present study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Muribaculaceae is a freshly renamed family, which is formerly named as S24-7 . It has been reported that Muribaculaceae is positively correlated with immune response including natural killer cell and NF-κB signaling, and the family members of Muribaculaceae can interact with both innate and adaptive immune responses via IgA coating . Rikenellaceae, reported to present a higher relative abundance in ovalbumin/staphylococcal enterotoxin B-sensitized mice, was found to be reduced by AA-2βG in our present study.…”
Section: Discussionsupporting
confidence: 65%
“…57 It has been reported that Muribaculaceae is positively correlated with immune response including natural killer cell and NF-κB signaling, 58 and the family members of Muribaculaceae can interact with both innate and adaptive immune responses via IgA coating. 59 Rikenellaceae, reported to present a higher relative abundance in ovalbumin/ staphylococcal enterotoxin B-sensitized mice, 60 was found to be reduced by AA-2βG in our present study. Similarly, the relative abundance of Rikenellaceae in both IBD mouse models and long-term intervened normal mouse models was reduced by AA-2βG.…”
Section: ■ Discussionsupporting
confidence: 63%
“…A similar expansion of Clostridia species was also detected in our study and recapitulated in IgA-deficient IL-10 −/− mice. Recently, minimal distortion of the resident microbiota composition was found in β7 −/− mice under homeostatic conditions, despite significant perturbation of the intestinal B-cell compartment 33 . However, it is possible that a baseline dysregulation of the microflora that is known to occur in inflamed IL-10 −/− mice 34 is required for the accentuated effect of β7/IgA deficiency to take place.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 PIgR transcripts were clearly increased, suggesting that the epithelium senses the intraluminal IgA deficit, likely though TLR engagement of pathogen-associated molecular patterns, originating from an altered microbiota composition. 38 In the ileal LP, we found 3 main B cell subsets, based on their expression of CD19 (shed upon class switching) and surface IgA. The CD19 + cells appeared to be in their earliest state of maturation as they had the highest nucleocytoplasmic ratio, expressed IgM, IgD, CCR7, and S1PR1.…”
Section: Discussionmentioning
confidence: 92%